Antibacterial and Antifungal Activity of Carica papaya L. Seed Extracts: A Recent Study - Sundar, S.; Padmalatha, K.; Reddy, A. Jayarami; Bhavana, A.; Neeraja, N. K. S.; Keertana, S. Jaya Sai (Challenges and Advances in Pharmaceutical Research Vol. 10, 2022)
Antimicrobial agents are abundant in medicinal plants. Many powerful and useful medications are derived from medicinal plants, which are used in various countries. Carica papaya roots, fruits, bark, seeds, and pulp have been shown to have therapeutic effects. It has been used to treat conditions such as eczema, warts, sinusitis, cutaneous tubercles, dyspepsia, blood pressure, amenorrhoea, and constipation. Carica papaya is a more important medicinal herb that is used as a folk medicine for the treatment of different disorders all over the world. Carica papaya seeds were approved and confirmed in some studies for their effective anthelmintic properties against nematodes found in animals. It is a member of the Caricaceae family. Carica papaya (Papaya) seeds were extracted using a soxhlet apparatus using solvents such as ethanol, methanol, and chloroform. The antibacterial and antifungal activity of extracts at various concentrations (50, 100, and 150 \(μ\)g/ml) was examined using the agar disc diffusion method with three gramme positive, three gramme negative bacteria, and two fungal species. For antibacterial and antifungal activities, gentamicin and fluconazole were chosen as standard medicines. Methanol and chloroform extracts inhibited gramme negative germs more effectively than ethanol extract. Ethanol and chloroform extracts demonstrated a larger zone of inhibition (10-15 mm) than methanol extract for gramme positive microorganisms. Candida albicans exhibited a 15, 16 mm zone of inhibition in chloroform and methanol extracts at concentrations of 150 \(μ\)g/ml, respectively. Similarly, Aspergillus niger exhibited a zone of inhibition of 11, 13 mm in 150 \(μ\)g/ml methanol and chloroform extracts, respectively. According to the findings of these investigations, Carica papaya seed extracts have very strong antibacterial and antifungal activity in both methanol and chloroform extracts.